3D concrete printing technology : construction and building applications - Sanjayan, Jay G.; Nazari, Ali; Nematollahi, Behzad (Butterworth-Heinemann, an imptint of Elsevier, 2019)
3D Concrete Printing Technology provides valuable insights into the new manufacturing techniques and technologies needed to produce concrete materials. In this book, the editors explain the concrete printing process for mix design and the fresh properties for the high-performance printing of concrete, along with commentary regarding their extrudability, workability and buildability. This is followed by a discussion of three large-scale 3D printings of ultra-high performance concretes, including their processing setup, computational design, printing process and materials characterization. Properties of 3D-printed fiber-reinforced Portland cement paste and its flexural and compressive strength, density and porosity and the 3D-printing of hierarchical materials is also covered.